Protocol for a Cross-Sectional Study: Effects of a Multiple Sclerosis Relapse Therapy With Methylprednisolone on Offspring Neurocognitive Development and Behavior (MS-Children) - Kozik, Valeska; Schwab, Matthias; Thiel, Sandra; Hellwig, Kerstin; Rakers, Florian; Dreiling, Michelle (Frontiers in Neurology, 2022)
Introduction: Multiple Sclerosis (MS) is the most common neuroimmunological disease in women of childbearing age. Current MS therapy consists of immunomodulatory relapse prevention with disease-modifying therapies (DMTs) and acute relapse therapy with the synthetic glucocorticoid (GC) methylprednisolone (MP). As most DMTs are not approved for use during pregnancy, treatment is usually discontinued, increasing the risk for relapses. While MP therapy during pregnancy is considered relatively save for the foetus, it may be detrimental for later cognitive and neuropsychiatric function. The underlying mechanism is thought to be an epigenetically mediated desensitisation of GC receptors, the subsequent increase in stress sensitivity, and a GC-mediated impairment of brain development. The aim of this study is to investigate the associations of foetal MP exposure in the context of MS relapse therapy with later cognitive function, brain development, stress sensitivity, and behaviour. Methods and analysis: 80 children aged 8 to 18 years of mothers with MS will be recruited. 40 children, exposed to GC in utero will be compared to 40 children without foetal GC exposure. The intelligence quotient will serve as primary outcome. Secondary outcomes will include attention, motor development, emotional excitability, Attention-Deficit Hyperactivity Disorder-related symptoms, and behavioural difficulties. The Trier Social Stress Test will test stress sensitivity, EEG and MRI will assess functional and structural brain development. To determine underlying mechanisms, DNA methylation of the GC receptor gene and the H19/IGF2 locus and changes in the microbiome and the metabolome will be investigated. Primary and secondary outcomes will be analysed using linear regression models. Time-variant outcomes of the stress test will be analysed in two mixed linear models exploring overall activity and change from baseline. Ethics and dissemination: This study was approved by the participating institutions’ ethics committees and results will be presented in accordance with the STROBE 2007 Statement. Trial registration: https://clinicaltrials.gov/ct2/show/NCT04832269?id=ZKSJ0130